Eksistensi Dakwah Bil Hikmah sebagai Akselerasi Pengembangan Sosial Keagamaan di Kecamatan Sukadana Lampung Timur - Anton Widodo; Nur Fauziah Fatawi; Andi Rahmad (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
Da’i is agents of change who bring ideas and provide innovations for changes in people’s lives for the better. As agents of change, many abilities are needed to enable the role of preachers to successfully change society in terms of knowledge, attitudes and behavior, one of which is the ability to convey da’wah messages through tabligh and the ability to communicate. The focus of this research is how Da’is in Sukadana, East Lampung Regency carry out proselytization and carry out missions as agents of change. This research is a phenomenological study so that the interpretive paradigm uses a phenomenological approach. Research data collection was carried out by observation, documentation and interviews, involving five Da’i as research objects. The results showed that the Da’i experience in carrying out dakwah bil hikmah was claimed to have succeeded in bringing about positive changes in the Sukadana community. Da’is in Sukadana have outstanding abilities and are successful in their preaching by preaching bil hikmah. Their proselytization is carried out through religious, social guidance and proselytizing activities by providing information and ideas to change the Sukadana community into obedient and devout people to Allah and be accepted by other communities. Da’is in conveying da’wah messages through tabligh in Sukadana District are under informative and educational functions with proselytizing activities through Majlis Taklim, Friday sermons and other non-formal lectures. This finding confirms that the dakwah bil hikmah should continue to be used as an ideal missionary in Islamic society.